(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Dental aesthetics has emerged as a paramount concern in everyday life due to its direct impact on self-confidence, self-esteem, and overall quality of life. Patient satisfaction measures how well healthcare services meet patients' needs and expectations and provide an acceptable standard of care. It serves as an indicator of healthcare quality and factors regarding restoration, restoration types, and color in restoration. This study aims to assess the degree of satisfaction and related influencing factors among patients in Saudi Arabia who had anterior composite restorations, fixed prostheses, and removable prostheses. Methods: A cross-sectional questionnaire survey the population under study comprised adult Saudis of varying ages and genders who had undergone various anterior restorative procedures (crown, veneer, bridge, composite restoration, and denture). The sample recruitment strategy relied on social media platforms. Results: Regarding the satisfaction levels about dental restorations, a majority reported positive feelings towards the general appearance (47.3%) and quality texture (47.3%) of their restorations. In term of the influence factors regarding restoration satisfaction, dissatisfaction was particularly evident regarding color, with 17.6% expressing dissatisfaction, and concerns about alignment and size also emerged. Conclusively, 29.2% reported a high level of satisfaction, while only 8.2% indicated moderate satisfaction. The data highlights a concerning 62.6% of respondents expressing low satisfaction. Conclusion: This study highlights the essential components of patient satisfaction with dental restorations in Saudi Arabia, particularly focusing on anterior composite restorations and fixed and removable prostheses. The findings reveal a significant gap in satisfaction levels, with only 29.2% of respondents reporting high satisfaction and a striking 62.6% expressing low satisfaction, predominantly linked to color, alignment, and size of restorations.